2017
DOI: 10.1007/s00231-017-2133-1
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer nanofluid based on curly ultra-long multi-wall carbon nanotubes

Abstract: The main challenge in the use of multi-wall carbon nanotube (MWCNT) as key components of nanofluids is to transfer excellent thermal properties from individual nanotubes into the bulk systems. We present studies on the performance of heat transfer nanofluids based on ultra-long (~2 mm), curly MWCNTs -in the background of various other nanoC-sp 2 , i.e. oxidized MWCNTs, commercially available Nanocyl™ MWCNTs and spherical carbon nanoparticles (SCNs). The nanofluids prepared via ultrasonication from water and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…13 (7), 130 (5), 117 (20), 99 (100), 81 (6), 71 (23), 57 (27), 43 (80). (5), 155 (4), 142 (4), 127 (5), 112 (24), 99 (100), 83 (10), 71 (24), 57 (23), 43 (61).…”
Section: ■ Experimental Sectionunclassified
“…13 (7), 130 (5), 117 (20), 99 (100), 81 (6), 71 (23), 57 (27), 43 (80). (5), 155 (4), 142 (4), 127 (5), 112 (24), 99 (100), 83 (10), 71 (24), 57 (23), 43 (61).…”
Section: ■ Experimental Sectionunclassified
“…1A ). Those areas range from microelectronics (field-effect transistors, 3,4 microprocessors 5 ), stealth technology, 6 energy storage, 7,8 heat transfer, 9 composite materials, 10,11 functional coatings 12 and films 13,14 to, key here, biotechnology and medicine (drug delivery, 15–17 biosensors 18,19 ). The list is incomplete while the indicated areas naturally intertwine and cross-inspire.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this limitation may be overcome by employing nanofluids (NFs) which constitute a prospective solution in the design and manufacture of the modern HTFs. The most intensively studied carbon nanotube-based NFs are based on EG , and, recently, on ionic liquids. , Although 1,2-PG and 1,3-PG have many advantages, multi-walled carbon nanotube (MWCNT)-based NFs with propanediols as base fluids are rarely investigated. , Boncel et al found that 1,3-PG-based NFs containing 0.53 vol % curly ultra-long MWCNTs, stabilized with gum arabic in water, emerged as 39% more heat-conducting than pristine 1,3-PG. Nevertheless, the rheological characteristics and NF stability at high MWCNT concentrations were not cross-verified.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Although 1,2-PG and 1,3-PG have many advantages, multi-walled carbon nanotube (MWCNT)-based NFs with propanediols as base fluids are rarely investigated. 6,12 Boncel et al 12 found that 1,3-PG-based NFs containing 0.53 vol % curly ultra-long MWCNTs, stabilized with gum arabic in water, emerged as 39% more heat-conducting than pristine 1,3-PG. Nevertheless, the rheological characteristics and NF stability at high MWCNT concentrations were not cross-verified.…”
Section: ■ Introductionmentioning
confidence: 99%